2018
DOI: 10.1155/2018/1042576
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Spa Therapy, Mud-Pack Therapy, Balneotherapy, and Mud-Bath Therapy in the Management of Knee Osteoarthritis. A Systematic Review

Abstract: Background Osteoarthritis (OA) is the most common musculoskeletal disease in the world. OA is the result of an inflammatory and degenerative process affecting the entire joint. Osteoarthritis, especially involving the knee, has a relevant socioeconomic impact in terms of drugs, hospital admissions, work absences, and temporary or permanent invalidity. Therapy of knee osteoarthritis is based on pharmacological and nonpharmacological measures. Methods We conducted a systematic review of the studies published bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 43 publications
1
31
0
2
Order By: Relevance
“…As mentioned in the results, we found that the group which received peat intervention had a greater decrease in VAS than the control group with statistical significance. Several studies using VAS as a measure of knee pain have demonstrated the effectiveness of pelotherapy for pain relief [19,[29][30][31][32]. In particular, several studies have confirmed that pain relief persists even after long-term follow-up of 6 months or longer [30,32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As mentioned in the results, we found that the group which received peat intervention had a greater decrease in VAS than the control group with statistical significance. Several studies using VAS as a measure of knee pain have demonstrated the effectiveness of pelotherapy for pain relief [19,[29][30][31][32]. In particular, several studies have confirmed that pain relief persists even after long-term follow-up of 6 months or longer [30,32].…”
Section: Discussionmentioning
confidence: 98%
“…Balneotherapy is a traditional treatment for musculoskeletal disorders in various countries, and many studies have reported its effects on pain in OA patients. Mud-pack therapy, mud-bath therapy, bath therapy, and spa therapy have proven to be effective in reducing pain and NSAID consumption and improving the quality of life in patients with knee OA [19].…”
Section: Introductionmentioning
confidence: 99%
“…Balneotherapy has also been proved to have beneficial effects on patients with osteoarthritis. Osteoarthritis is a degenerative musculoskeletal disease and leading cause of pain, disability, and impaired quality of life [4,10,11]. It affects synovial joints (mainly hips and knees), in which cartilage destruction, subchondral bone remodeling, osteophyte formation, and synovial inflammation are found, thereby leading to joint stiffness [11].…”
Section: Therapeutic Properties Of Natural Medicinal Resourcesmentioning
confidence: 99%
“…It affects synovial joints (mainly hips and knees), in which cartilage destruction, subchondral bone remodeling, osteophyte formation, and synovial inflammation are found, thereby leading to joint stiffness [11]. Osteoarthritis usually affects approximately 10% of people over 60 years of age [10]. Different clinical trials were conducted to evaluate the effectiveness of balneotherapy in patients with osteoarthritis.…”
Section: Therapeutic Properties Of Natural Medicinal Resourcesmentioning
confidence: 99%
“…Estudios previos han encontrado resultados prometedores en enfermedades reumatológicas como artritis reumatoide [3] , lumbalgias [4] , fibromialgia [5] , y enfermedades dermatológicas como psoriasis o dermatitis atópica [6] . Asimismo, el tratamiento de diversas afecciones por medio del uso de aguas termales fue considerado por la Organización Mundial de la Salud, como un recurso a tener en cuenta en la mejora del bienestar y la calidad de vida de pacientes con enfermedades crónicas [7] .…”
Section: Introductionunclassified